Co-receptor signaling in the pathogenesis of neuroHIV - E. A. Nickoloff-Bybel; L. Festa; O. Meucci; P. J. Gaskill (Retrovirology, 2021)
Abstract The HIV co-receptors, CCR5 and CXCR4, are necessary for HIV entry into target cells, interacting with the HIV envelope protein, gp120, to initiate several signaling cascades thought to be important to the entry process. Co-receptor signaling may also promote the development of neuroHIV by contributing to both persistent neuroinflammation and indirect neurotoxicity. But despite the critical importance of CXCR4 and CCR5 signaling to HIV pathogenesis, there is only one therapeutic (the CCR5 inhibitor Maraviroc) that targets these receptors. Moreover, our understanding of co-receptor signaling in the specific context of neuroHIV is relatively poor. Research into co-receptor signaling has largely stalled in the past decade, possibly owing to the complexity of the signaling cascades and functions mediated by these receptors. Examining the many signaling pathways triggered by co-receptor activation has been challenging due to the lack of specific molecular tools targeting many of the proteins involved in these pathways and the wide array of model systems used across these experiments. Studies examining the impact of co-receptor signaling on HIV neuropathogenesis often show activation of multiple overlapping pathways by similar stimuli, leading to contradictory data on the effects of co-receptor activation. To address this, we will broadly review HIV infection and neuropathogenesis, examine different co-receptor mediated signaling pathways and functions, then discuss the HIV mediated signaling and the differences between activation induced by HIV and cognate ligands. We will assess the specific effects of co-receptor activation on neuropathogenesis, focusing on neuroinflammation. We will also explore how the use of substances of abuse, which are highly prevalent in people living with HIV, can exacerbate the neuropathogenic effects of co-receptor signaling. Finally, we will discuss the current state of therapeutics targeting co-receptors, highlighting challenges the field has faced and areas in which research into co-receptor signaling would yield the most therapeutic benefit in the context of HIV infection. This discussion will provide a comprehensive overview of what is known and what remains to be explored in regard to co-receptor signaling and HIV infection, and will emphasize the potential value of HIV co-receptors as a target for future therapeutic development.